Seminar Kewirausahaan - Peran Pemuda Kristen Dan Peluang Bisnis Di Era Society 5.0 - Mince Batara; Agustinus Mantong; Dina Ramba; Abedneigo C. Rambulangi; Andrew Ridow Johanis M (Jurnal Pelayanan Hubungan Masyarakat, 2023)
The church is a community, like organizations in general, the church has an important role in the lives of its congregation members. In the organizational structure, each church has an intra-ecclesiastical administrator. The Administrators of each congregation will be representatives of each congregation. OIG category PPGT Klas Rembon Sado'ko' held an entrepreneurship seminar with the aim of providing knowledge, motivation and finding business opportunities. Entrepreneurship seminar activities in the Sub Theme: The Role of Christian Youth and finding opportunities in the era of society 5.0. This activity was attended by more than ± 100 people.